Моніторинг прісноводних об'єктів на сході України в умовах повномасштабних військових дій - Штефан, С. О.; Бабенко, Володимир Миколайович (Яроче́нко Я. В., 2025)
Based on the processing of open sources of information and statistical data on the state of freshwater bodies in the south and east of Ukraine, a theoretical model has been created for monitoring and short-term forecasting of the impact of full-scale military operations on them. Preliminary numerical calculations of the consequences of changes in the natural environment have been carried out. The research is part of the student work on applying a monitoring system for implementing environmental protection technologies.
'
Keywords: моніторингові мережі; довкілля; водні об'єкти; космічний дистанційний моніторинг; військовий стан